Comparative study for the production of monoclonal antibodies in single‐use vs stainless steel bioreactors based on product quality and stress factor. Issue 7 (15th July 2020) - Beck, Christian; Werz, Silke; Herrmann, Alexander; Meiringer, Christoph T. A.
Abstract : The article shows general comparability for MABs produced in stainless steel and single‐use bioreactors under GMP conditions in clinical manufacturing. The outcome of the study is that SUBs and SSBs can produce MABs with comparable cell culture performance and product quality. This general comparability paves the way for SUBs to produce new and existing products for (clinical) manufacturing. Abstract: Single‐use bioreactors (SUB) and stainless steel bioreactors (SSB) differ in their physical properties. This can have an effect on the performed processes. To be able to guarantee flexible planning in a facility, any kind of processes in SUB and SSB must be sufficiently similar. To date, assessments of SUB and SSB have been exclusively specific for one single product. This study shows a general nonproduct‐specific comparison of the production of different types of monoclonal antibodies in different scales of SUBs and SSBs. The study is set up with 72 clinical manufacturing fermentation runs in total by comparing the cell culture performance and quality attributes of these two bioreactor systems. The outcome is that SUBs and SSBs can produce monoclonal antibodies with comparable cell culture performance and product quality. This general comparability paves the way for SUBs to produce new and existing products for (clinical) manufacturing.